A framework of the energy-efficient vehicle initiative and its implementation in a developed country: the case of Malaysia - Daud, Farrah Effa; Ponrahono, Zakiah; A. A., Fatiah; Ab Rahman, Syakir Amir; Sahrir, Syazwani (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2021)
Energy-Efficient Vehicles (EEV) are a form of green transportation that minimise carbon dioxide emissions and eliminate reliance on fossil fuels. As an oil-producing nation, Malaysia needs to conserve its resources and alternate its dependence on fuel combustion engines and their toxic emissions. In recent years, Malaysia has set EEV production goals and adopted several policies to reduce greenhouse gas emissions while meeting the transportation sector's growing energy demands. This study evaluates the current policies and initiatives for EEV and their relevance and implementation in the present scenario. It is worth ascertaining the critical elements that need to be in place for the government to push for the adoption of EEV. This study first reviewed relevant government policies supporting EEVs. Next, a comparative analysis of EEVs initiatives between Asia-Pacific Economic Cooperation countries was discussed. Simultaneously, expert panels were consulted through interview sessions to identify gaps in the implementation of EEVs. Based on the findings, the relationship framework of EEVs initiatives and an outline of strategies to improve existing practices were formulated. As a result, this study proposed integrating various agencies and market players as an essential factor to determine the success of implementing EEVs. By way of conclusion, a summary of effective policies is put forward as a recommendation to stimulate the current EEV market. This study sets the stage for policymakers to adopt and improve EEV strategies.